Regional differentiation of the tax burden on personal income in Canada - I. V. Mitroshin (Вестник университета)
The income of citizens reflects the degree of economic development of the country, and in the regional aspect – the degree of economic development of each region. Canada is very similar to Russia in its geographical location, nature and climate, so the standard of living of the population in this country is of interest. One of its indicators is the income of citizens. The state’s approach to personal income taxation reflects the general socio-economic policy in the country. The study analysed the tax burden on personal income in the provinces of Canada in 2000–2022, determined the dynamics of this indicator for the period under review, and identified the existence of correlation between the amount of income and the tax burden on it in the regional aspect. The results obtained found that in Canada, there is a conditional division into eastern provinces with a traditionally high tax burden, western provinces with a national average tax burden, and northern territories with a relatively low tax burden. A certain inverse relationship between the amount of citizens’ income and the tax burden on it has been established. In regions with high incomes, the tax burden is usually lower, and in regions with low incomes, it is generally higher. However, there are regions that are exceptions, which shows the relative financial independence of regional authorities in Canada. The dynamics of the tax burden on personal income in the analysed period reflected the impact of the crises of 2008 and 2020 when it decreased. This fact demonstrates the sensitive response of regional governments to the changing economic situation.